Customer awareness towards the existence of Sinar Card: a case study on Sinar Suci Sdn Bhd / Suryatie Hj. Alwi Umar - Hj. Alwi Umar, Suryatie (2006)
Sinar Suci is an independent general bookstore operating at Jalan Haji Taha, Kuching, Sarawak. With nearly two decades of experience in the book business, involving not just retail bookstore operations but also as a contractor for the supply of books, office equipment and stationeries to schools and libraries, universities and colleges, government agencies and also the private sectors. Established on 22nd November, 1977, Sinar Suci has established itself as a reputable, experienced and reliable supplier and distributor of local books. Sinar Suci is a sole distributor for Dewan Bahasa dan Pustaka (DBP) in Sarawak and it has been well known in distributing and selling textbooks for both primary and secondary schools. Sinar Suci offers competitive price, which come with guaranteed quality service and products. The types of products that Sinar Suci offers to customers are books that cover different field such as, economics, laws, management, engineering, motivation, dictionaries, religion, magazines, novels and stationeries. Apart from that, it also offer services such as transportation, exhibition, credit sales, and medical equipment. Sinar Suci has constantly maintained a team of fully qualified and well- motivated employees working towards customer’s satisfactions. Sinar Suci’s aim is to keep its customers updated on the latest publication and offer them friendly services.